Valuation of sustainable design of the bilingual strategy for the protection of water resources - Vovk Korže, Ana (Journal for Geography, 2015)
The area of Pomurje, Spodnje Podravje and Međimurje have in common geographical, cultural, developmental and environmental characteristics. The pollution of underground and surface water is a consequence of burdens from dispersed sources of intensive agriculture and dispersed urbanization. These are also the characteristics of the whole cross-border project area. The strategy followed the example of the regular estimation techniques of the influence of spatial intervention on the environment and later on also expending into a method of strategic environmental estimation. For the valuation of the sustainable design of bilingual strategy the M4K that was developed by English “green” economist Paul Ekins (2008), was used. The strategy followed the example of the regular estimation techniques of the influence of spatial intervention on the environment and later on also expending into a method of strategic environmental estimation. Assessment of measurements for reaching sustainability shows a poor connection between capitals because the measurements are divided into sectors.